A Humean Approach to the Boundaries of Morality. Issue 1 (March 2020) - Collier, Mark
Abstract : Hume maintains that the boundaries of morality are widely drawn in everyday life. We routinely blame characters for traits that we find disgusting, on this account, as well as those which we perceive as being harmful. Contemporary moral psychology provides further evidence that human beings have a natural tendency to moralize traits that produce feelings of repugnance. But recent work also demonstrates a significant amount of individual variation in our sensitivities to disgust. We have sufficient reason to bracket this emotion, therefore, when adopting the general point of view: if we allow idiosyncratic affective responses to shape our fully considered moral judgments, we could no longer reasonably expect spectators with different sensitivities to agree with us.